Virtual PSLLT 2022
DOI: 10.31274/psllt.13351
|View full text |Cite
|
Sign up to set email alerts
|

Mastering EFL Pronunciation in North Macedonia and Poland: A Quantitative Questionnaire Approach

Abstract: This paper examines the issue of the mastering of EFL pronunciation among 144 students of English studies in North Macedonia (n=34) and Poland (n=110) by means of a questionnaire consisting of: 23 scalar judgments and 4 closed questions. The responses to the questions provide information on: the best place to study pronunciation, the preferred English accent, the types of communication problems and the general awareness of the informants' own pronunciation problems. The results of the judgments confirm a very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Growing research has examined EFL learners’ and teachers’ beliefs about ‘native speakers' and attitudes toward Inner Circle Englishes. A recurring finding in the literature has been that teachers and learners of English in Poland overwhelmingly target Inner Circle norms (Mystkowska‐Wiertelak & Bielak, 2014; Nowacka, 2022; Paciorkowski, 2022a; Szymańska‐Tworek, 2021; Szymańska‐Tworek & Sycz‐Opoń, 2020). Research has also suggested that teachers and learners of English tend to strongly believe in the traditional division between ‘native' and ‘non‐native speakers’ (Mystkowska‐Wiertelak & Bielak, 2014).…”
Section: English In the Polish Educational Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Growing research has examined EFL learners’ and teachers’ beliefs about ‘native speakers' and attitudes toward Inner Circle Englishes. A recurring finding in the literature has been that teachers and learners of English in Poland overwhelmingly target Inner Circle norms (Mystkowska‐Wiertelak & Bielak, 2014; Nowacka, 2022; Paciorkowski, 2022a; Szymańska‐Tworek, 2021; Szymańska‐Tworek & Sycz‐Opoń, 2020). Research has also suggested that teachers and learners of English tend to strongly believe in the traditional division between ‘native' and ‘non‐native speakers’ (Mystkowska‐Wiertelak & Bielak, 2014).…”
Section: English In the Polish Educational Systemmentioning
confidence: 99%
“…Both groups also tend to equate Inner Circle Englishes—especially British English—with sounding more professional, intelligible, credible and with being more competitive on the job market (Paciorkowski, 2022a; Szymańska‐Tworek & Sycz‐Opoń, 2020). Furthermore, some Polish pre‐service teachers have expressed negative attitudes toward English used by Polish speakers, explaining that Polish English sounds ‘harsh', ‘incorrect' and even ‘stupid’ (Nowacka, 2022, pp. 57, 63).…”
Section: English In the Polish Educational Systemmentioning
confidence: 99%